2015
DOI: 10.1097/mpg.0000000000000719
|View full text |Cite
|
Sign up to set email alerts
|

Parental and Youth Understanding of the Informed Consent Process for Pediatric Endoscopy

Abstract: Understanding of IC performed for pediatric endoscopy could be improved in both parents and youth. Our findings suggest that interventions targeting parents, youth, and physicians may be helpful. Further study is needed to determine whether our findings are representative of IC understanding at other pediatric endoscopy centers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 41 publications
3
16
0
Order By: Relevance
“…In a study on obtaining informed consent from patients before surgical operations in Iran, it was shown that information given to the patients was insufficient and patients were not provided with enough information about the operation, type of anesthesia, possible complications, alternative treatments, period of hospitalization, and postsurgery care (14), which is in agreement with the findings of the present study. As can be seen, in questions 13 and 14 (informing the child about diagnostic and treatment procedures and considering the child's opinion in the final decision), the physicians mostly answered "in most cases no" and "sometimes", respectively.…”
Section: Discussionsupporting
confidence: 90%
“…In a study on obtaining informed consent from patients before surgical operations in Iran, it was shown that information given to the patients was insufficient and patients were not provided with enough information about the operation, type of anesthesia, possible complications, alternative treatments, period of hospitalization, and postsurgery care (14), which is in agreement with the findings of the present study. As can be seen, in questions 13 and 14 (informing the child about diagnostic and treatment procedures and considering the child's opinion in the final decision), the physicians mostly answered "in most cases no" and "sometimes", respectively.…”
Section: Discussionsupporting
confidence: 90%
“…While performance of IC for procedures involving significant risk is legally mandated, many IC studies of adult patients and parents of pediatric patients have demonstrated suboptimal comprehension of key IC elements 3 4 5 6 . Similarly, we demonstrated poor comprehension of key IC elements by children and adolescents undergoing pediatric endoscopy 7 .…”
Section: Introductionmentioning
confidence: 63%
“…We employed a randomized controlled study design to evaluate the efficacy of a video intervention augmenting IC discussions in improving parental and youth IC comprehension. Sample size was based on our prior work and selected to detect a 30 % difference in comprehension scores between the intervention v. control group 7 . The local Institutional Review Board approved the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has demonstrated communication pitfalls, such as clinician tendencies to be verbally dominant, ask few open-ended questions, and often neglect to respond to patient fears with direct empathy 38,39 . Furthermore, parents often exhibit limited understanding about their children’s medical conditions and treatment options 40,41 . This may limit opportunity for parents or patients to gather information and express concerns during consultations.…”
Section: Discussionmentioning
confidence: 99%